Intake of n-3 fatty acids and long-term outcome in renal transplant recipients: a post hoc analysis of a prospective cohort study. Issue 12 (20th December 2016) - Pranger, Ilse G.; Gruppen, Eke G.; van den Berg, Else; Soedamah-Muthu, Sabita S.; Navis, Gerjan; Gans, Rijk O. B.; Muskiet, Frits A. J.; Kema, Ido P.; Joosten, Michel M.; Bakker, Stephan J. L.
Abstract: Supplementation with n -3 fatty acids may improve long-term outcomes of renal transplant recipients (RTR). Recent evidence suggests that EPA and DHA have different outcomes compared with α -linolenic acid (ALA). We examined the prospective associations of EPA–DHA and ALA intakes with graft failure and all-cause mortality in 637 RTR. During 3·1 years (interquartile range 2·7, 3·8) of follow-up, forty-one developed graft failure and sixty-seven died. In age- and sex-adjusted analyses, EPA–DHA and ALA intakes were not associated with graft failure. EPA–DHA intake was not significantly associated with mortality (hazard ratio (HR) 0·79; 95% CI 0·54, 1·15 per 0·1 energy% difference). ALA intake was significantly associated with mortality (HR 1·17; 95% CI 1·04, 1·31 per 0·1 energy% difference). This association remained following adjustments for BMI, proteinuria and intakes of fat, carbohydrate and protein. RTR in the highest tertile of ALA intake exhibited about 2-fold higher mortality risk (HR 2·21; 95% CI 1·23, 3·97) compared with the lowest tertile. In conclusion, ALA intake may be associated with increased mortality in RTR. Future RCT are needed to confirm these results.